The meaning and experience on nationalism among Indonesian migrant workers’ children in border area - Yoyon Suryono; Zamroni Zamroni; Johan Irmansyah; Dendi Tri Suarno; Faishal Yasin (Institute of Advanced Engineering and Science, 2022)
Discussion related to nationalism has become an essential topic in the field of Indonesian education, particularly in the context of education in the border area. This study reported on the condition of educational services, and explored the meaning and experience of nationalism from Indonesian migrant workers' (IMW's) children at the community learning center (CLC) Sarawak, Indonesia-Malaysia border area. The study employed qualitative methods with a phenomenological approach, intended to produce in-depth data on the meaning and experience of nationalism from IMW's children attending CLC Sarawak, Malaysia. The data collected in this study used the main data through exhaustive interviews and observation, while additional data was collected through documentation. The results showed that CLC has made the optimal efforts in growing IMW's children nationalism in border areas, included: i) Implementing educational curriculum in accordance with curriculum standards in Indonesia; ii) Implement programs that can increase IMW's children nationalism; and iii) Improve access and quality education services for IMW's children in border areas. Furthermore, IMW's children interpret nationalism as a feeling of love, pride, and willingness to sacrifice for the nation and country with all their heart. The meaning of nationalism is constructed through various children’s experiences obtained in the school environment, family environment, and socio-cultural conditions in the community. The results and discussions reported in this study can serve as a reference and guideline for the Indonesian government to formulate and prioritize educational designs or policies for Indonesian migrant workers in border areas.